PKM OF SMALL INDUSTRY OF BRICKS IN ULUALE SUB-DISTRICT WATANG PULU DISTRICT SIDENRENG RAPPANG REGENCY SOUTH SULAWESI PROVINCE - Panennungi, Panennungi (Universitas Negeri Yogyakarta, 2018)
The purpose of this Community Partnership Program activity is to give rise the knowledge and ability of both partners in establish their efford, whether on production aspect and management aspect.The goal of this activity is (1) partners have proper knowledge and skill to raise: (1) product quantity of brick, (2) product quality of brick, (3) brick management and marketing, and (4) brick marketing profit. Approaching methods used to overcome agreed problem together are: (1) to enhance both partners' quantity of bricks, used methods are: explanation and discussion, (2) to enhance both partners' quality of bricks, used methods are: explanation, feedback discussion, demonstration, and training, (3) to enhance management and marketing skill, used methods are: explanation and feedback discussion, and (4) to increase both partners' product of brick marketing profits, used methods are: explanation, feedback discussion, demonstration, and training. The attained results of this Commnity Service are partners have had proper knowledge and skill to raise: (1) product quantity of bricks, (2) product quality of bricks, (3) bricks management and marketing, and (4) brick's marketing profit.